SUBEPIDURAL HEMATOMA IN STROKE: A RARE BUT CRITICAL CONSIDERATION IN ADULT PATIENTS - Ibragimov Sardorbek Tolib o’g’li,; Shokirova Mehruza Komiljon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Subepidural hematoma (SEH) is an uncommon yet potentially life-threatening condition that can arise in the context of cerebrovascular events, including ischemic  and  hemorrhagic  strokes.  Unlike  epidural  and  subdural  hematomas,  SEH occurs  in  the  dural  border  zone,  presenting  unique  diagnostic  and  management challenges.  This  article  explores  the  pathophysiology,  clinical  manifestations, neuroimaging characteristics, and therapeutic approaches for SEH in stroke patients, emphasizing  its  role  in  secondary  neurological  deterioration.  Given  the  limited literature on this topic, we highlight key case reports, propose diagnostic algorithms, and discuss potential surgical and conservative treatment strategies.